2023
DOI: 10.1037/cfp0000177
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and relationship quality in dating relationships.

Abstract: Associations between higher religiosity and positive marital outcomes are well documented (e.g., Mahoney et al., 1999;Olson et al., 2015), but less attention has been paid to religiosity in unmarried relationships. This study examines associations between religiosity and relationship quality in a sample of individuals in early adulthood (N = 354) who were in serious but unmarried different-sex relationships (mean duration of 4 years). Individuals rated their own religiosity (overall religiousness and attendanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Next, in the current study, relationship quality was assessed in three domains, namely, perceived support, relationship conflict, and relationship depth. Prior studies have demonstrated that, in general, religiosity plays a crucial role in relationship maintenance for marriages (Langlais and Schwanz 2017) and for nonmarital and dating relationships (Aragoni et al 2021;Henderson et al 2018;Langlais and Schwanz 2017). Moreover, prayer for a partner has been recognized in past research as contributing to the improvement of relationship quality (e.g., Beach et al 2011;May et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, in the current study, relationship quality was assessed in three domains, namely, perceived support, relationship conflict, and relationship depth. Prior studies have demonstrated that, in general, religiosity plays a crucial role in relationship maintenance for marriages (Langlais and Schwanz 2017) and for nonmarital and dating relationships (Aragoni et al 2021;Henderson et al 2018;Langlais and Schwanz 2017). Moreover, prayer for a partner has been recognized in past research as contributing to the improvement of relationship quality (e.g., Beach et al 2011;May et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The review of the literature pertaining to praying for a partner and relationship outcomes reveals two key notions. First, the majority of the prior research on religion and praying in the context of relationships has largely focused on marital unions (Aragoni et al 2021;Henderson et al 2018;Langlais and Schwanz 2017). This focus is understandable, taking into account that religious involvement enhances the chances of marrying and religious attendance, and the salience of religion in daily life is considered a key factor in making decisions regarding starting cohabitation before or within marriage (Mahoney 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once they come to an understanding of religion, they can make their choice of which religion to practice or none of them at all. Couples who practiced the same religion reported to have higher levels of commitments and loyalty (Aragoni et al, 2021). Religious practices shapes individual's morals and values, and loyalty and commitment are an important part of many religions.…”
Section: Religiositymentioning
confidence: 99%
“…There are negative social consequences associated with these actions. Aragoni et al, (2021) stats in their research that there is a positive correlation to religiosity and positive martial outcomes. In their research, the couples reported having the same religious backgrounds.…”
Section: Religiositymentioning
confidence: 99%